Representasi Kepemimpinan Tokoh Utama dalam Anime ‘Dr. Stone’: Analisis Semiotika Peirce - Asri, Rina Afdhaliah; taqdir, Taqdir (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2025)
This study explores the semiotic representation of leadership embodied by the main character in the first season of the anime “Dr. Stone” directed by Shinya Iino. Utilizing Peirce’s semiotic theory, the research analyzes key scenes to uncover how visual and verbal signs construct the image of leadership within the context of Japanese popular culture. Data were collected through purposive sampling of selected episodes, focusing on narrative and character interactions that depict leadership values. The findings reveal that Senku Ishigami’s leadership is represented through specific icons, indexes, and symbols—such as scientific tools, gestures, and verbal affirmations—which collectively construct a unique leadership model that blends rationality, collectivism, and resilience. The study highlights how anime functions not only as entertainment but also as a medium for transmitting contemporary leadership values. The implications of this research suggest a need for broader cultural studies on leadership narratives in Japanese media, providing new insights for educators and scholars in language and cultural studies.